(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Researchers and practitioners in the field of services must prioritize learning about their targetaudience. Customers are spending more time online, which means more opportunities to collect usefuldata about their thoughts, feelings, and actions. The availability of client data online opens up newavenues for the development of tailored, high-caliber service. Successful service businesses need tofocus on customer understanding, which is why this area of study is so vital. Retailers, eateries, retailbanks, healthcare providers, government agencies, non-profits, and telecommunications corporationsare just few of the daily service providers that customers deal with. However, as a result of rapiddevelopments, especially in information technology, the context in which service is offered, experienced,and evaluated is shifting. Customers of modern service providers are increasingly engaged onlinebefore, during, and after their interactions with those providers, generating vast troves of data aboutthose interactions. Much of this data is already out there, and it can be used to provide better, moretailored service. However, one of the primary obstacles in present-day service marketing research andpractice is the collection and analysis of such massive data.